2014
DOI: 10.1007/978-3-662-44426-9_15
|View full text |Cite
|
Sign up to set email alerts
|

Open Government Data: Facilitating and Motivating Factors for Coping with Potential Barriers in the Brazilian Context

Abstract: Part 3: Policy and StakeholdersInternational audienceThe use of Open Government Data (OGD) involves multiple activities developed by networks of users with different capacities and goals, along a value chain. These users, and also government agents supplying OGD recognize benefits, motivations, barriers, facilitating and inhibiting factors in the process. This paper surveyed the perceptions of Brazilian OGD users and government agents, in order to provide information for the improvement of OGD supply and use

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 11 publications
(16 reference statements)
2
33
0
Order By: Relevance
“…In the inverse, if users have feedback, but no channel, the process will be hard to improve (and we lose impact insight too). Users that are not aware of OGD and its possibilities will not show Interest and Need [1,22,26,27]. Even if they have awareness and channels, they can express interest, to express need they require access to the organisation's metadata inventory.…”
Section: Discussionmentioning
confidence: 99%
“…In the inverse, if users have feedback, but no channel, the process will be hard to improve (and we lose impact insight too). Users that are not aware of OGD and its possibilities will not show Interest and Need [1,22,26,27]. Even if they have awareness and channels, they can express interest, to express need they require access to the organisation's metadata inventory.…”
Section: Discussionmentioning
confidence: 99%
“…Besides governmental oversight and monitoring of data quality standards, other additional benefits of OGD are the increased public value obtained through citizen participation and empowerment, and improved public relations and citizen attitude towards government [9,27]. A few challenges or barriers related to the use of OGD are difficulty for users in processing the information and the usability of the content available, since the information has typically been prepared by governments with a specific goal in mind [28]. Additionally, in order to adopt usage of OGD at the firm level, organizations need to have the support of top management [14,29].…”
Section: Business Intelligence and Open Government Datamentioning
confidence: 99%
“…Despite these challenges, OGD offers organizations the potential to unlock new innovative solutions that can incentivize entrepreneurship and generate economic value [8,9]. A review of the OGD literature suggests that the use of OGD can generate economic value and drive innovation within societies [28,30,31]. A survey of government employees and business professionals' use of OGD in Brazil revealed that this type of data promoted greater citizenship involvement [28].…”
Section: Business Intelligence and Open Government Datamentioning
confidence: 99%
“…For Janssen, Charalabidis and Zuiderwijk (2012) this motivation favors democratic accountability and citizenship. However, due to the cultural barrier of top management towards the availability of some OGD, it becomes difficult to promote this social participation (Albano & Reinhard, 2014). Thus, the actors reported having a concern about the accessibility of these data, seeking improvements in public policies in this process.…”
Section: 1mentioning
confidence: 99%
“…For Albano and Reinhard (2014), as seen by these data suppliers too, there is a low interest of government officials in collaborating with open data initiatives. These problems, together with the impasse in obtaining a uniform OGD policy (Martin et al, 2013), have a direct influence on the challenge of providing adequate support for both developers (with problems of collaboration and understanding of OGD), and for data suppliers (with little interaction between government levels and openness resistance from high government management).…”
Section: Differences and Similarities About The Improvements Reportedmentioning
confidence: 99%